Beyond the final whistle: vocational careers of retired soccer players of the female Swiss national team - Schmid, M. J.; Charbonnet, B.; Kurz, D.; Örencik, M.; Schmid, J.; Conzelmann, A. (Soccer & Society, 2024)
The present study surveyed 57 retired female soccer national team players to examine their athletic, educational, and vocational careers. The respondents achieved higher educational degrees compared to the general population. Contrasted with their siblings, no difference was found in school-leaving certificates and occupational prestige. Using cluster analysis, the following three clusters were found: (1) highly educated employees working in sports, (2) university graduates in liberal professions or executive-level employees, and (3) skilled workers and lower-grade white-collar workers. While the players in the first cluster mostly benefited from their engagement in elite soccer, the players in the other two clusters did not seem to be either positively or negatively influenced by it. However, the career paths of female soccer players will likely change in the coming years as investment in the sport and social recognition of women`s soccer continues to increase.